A Test and Characterisation Facility for Cryogenic Low Noise Amplifiers - Newton, Wesley (Department of Electrical Engineering, 2023)
This dissertation discusses how the receiver and the LNA contained within the receiver are the major contributors to the sensitivity. Furthermore, a method for testing and determining the equivalent noise temperature of a cryogenic LNA operating at a physical temperature of 20 K is selected and presented. This method was tested at the Klerefontein support base and the measurements allowed conclusions to be drawn that show that the uncertainty was unacceptable due to a few factors. One of the factors is the thermal gradient across the attenuator. This was investigated via a limited thermal study and a solution was proposed and implemented.